EPS Glycoconjugate Profiles Shift as Adaptive Response in Anaerobic Microbial Granulation at High Salinity - Gagliano, Maria C.; Neu, Thomas R.; Kuhlicke, Ute; Sudmalis, Dainis; Temmink, Hardy; Plugge, Caroline M. (Frontiers in Microbiology, 2018)
Anaerobic granulation at elevated salinities has been discussed in several analytical and engineering based studies. They report either enhanced or decreased efficiencies in relation to different Na+ levels. To evaluate this discrepancy, we focused on the microbial and structural dynamics of granules formed in two Upflow Anaerobic Sludge Blanket (UASB) reactors treating synthetic wastewater at low (5 g/L Na+) and high (20 g/L Na+) salinity conditions. Granules were successfully formed in both conditions, but at high salinity, the start-up inoculum quickly formed larger granules having a thicker gel layer in comparison to granules developed at low salinity. Granules retained high concentrations of sodium without any negative effect on biomass activity and structure. 16S rRNA gene analysis and Fluorescence in Situ Hybridization (FISH) identified the acetotrophic Methanosaeta harundinacea as the dominant microorganism at both salinities. Fluorescence lectin bar coding (FLBC) screening highlighted a significant shift in the glycoconjugate pattern between granules grown at 5 and 20 g/L of Na+, and the presence of different extracellular domains. The excretion of a Mannose-rich cloud-like glycoconjugate matrix, which seems to form a protective layer for some methanogenic cells clusters, was found to be the main distinctive feature of the microbial community grown at high salinity conditions.